Child Protection in Europe: Development of an International Cross-Comparison Model to Inform National Policies and Practices. (9th October 2014) - Spratt, Trevor; Nett, Jachen; Bromfield, Leah; Hietamäki, Johanna; Kindler, Heinz; Ponnert, Lina
Abstract : We report a five-nations project in comparative child protection to provide recommendations on policy and practice to inform the redevelopment of the Swiss child protection system. The Swiss Federal Government and the Optimus and Oak Foundations commissioned the project—collective title: Association Programme National pour la Protection de l'Enfant. We identify the historical developmental trajectories of child protection systems together with common drivers: the evidential basis for the prevalence and effects of child abuse, the co-joining of social and economic policies and practices to promote early investment in children, the influence of children's rights and comparative international league tables on child well-being . We describe the cross-national project methodology and analysis of results. Three key indicators for the performance of national child protection systems are indicated: creating a culturally sensitive child protection governance framework, building a relational heart and using evidence to inform policy and practice . These encapsulate the recommendations made with respect to the Swiss child protection system. The results provide a prototype model with potential utility in similar cross-national studies, and add weight to the argument that cross-cultural learning in the context of a globalised society is not only possible, but desirable.